Pendekatan dan Pengkajian Pendidikan Islam dalam Perspektif Filsafat - Daimah (LPPM IAINU Kebumen, 2019)
Philosophical thinking can be used in understanding religious teachings, with the intention that wisdom, essence or essence of religious teachings can be understood and understood carefully. Quoted from his book, according to piter Connolly There are five philosophical positions as approaches to Islamic studies. First, philosophy as religion, that is by reflecting on the nature of the highest reality of God's goodness. Second, philosophy as a servant of religion, namely reflection gives knowledge of God. Third, philosophy as a space maker for faith. Fourth, philosophy as a study of analysis of religion, and fifth is philosophy as a study of reasoning used in religious thought.